DETERMINASI PERTUMBUHAN EKONOMI DI PROVINSI JAWA BARAT (STUDI KOMMPARASI PEMERINTAH DAERAH KOTA DAN KABUPATEN - sutisna, shalhan hirzi; girindra mega paksi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Economic disparity among regions is a pivotal concern for equitable development. In West Java, Indonesia's most populous province, this issue is accentuated as several city and regency areas persistently lag in growth rates when compared to the provincial average. This study is dedicated to uncovering the determinants that may expedite the socioeconomic advancement of the most impoverished areas within the province over a significant period, from 2012 to 2021. Utilizing panel data regression analysis, this research meticulously examines a series of potential factors that could influence regional economic performance. The quantitative data for this comprehensive analysis were sourced from two authoritative Indonesian bodies: the Central Agency on Statistics (Badan Pusat Statistik - BPS) and the Directorate General of Fiscal Balance (Direktorat Jenderal Perimbangan Keuangan - DJPK). These datasets provide a robust foundation for assessing the fiscal, demographic, and economic variables that potentially contribute to the regional growth dynamics.